Health-related quality of life in patients given ciltacabtagene autoleucel for relapsed or refractory multiple myeloma (CARTITUDE-1): a phase 1b–2, open-label study. Issue 12 (December 2022) - Martin, Thomas; Lin, Yi; Agha, Mounzer; Cohen, Adam D; Htut, Myo; Stewart, A Keith; Hari, Parameswaran; Berdeja, Jesus G; Usmani, Saad Z; Yeh, Tzu-Min; Olyslager, Yunsi; Goldberg, Jenna D; et al.
Summary: Background: CARTITUDE-1 is a phase 1b–2 study evaluating ciltacabtagene autoleucel (cilta-cel), a chimeric antigen receptor T cell therapy with two B-cell maturation antigen–targeting single-domain antibodies, in patients with relapsed or refractory multiple myeloma. Primary efficacy outcomes have previously been reported. Here, we report health-related quality of life (HRQOL) secondary outcomes evaluated using patient-reported outcomes. Methods: This single-arm, open-label, phwase 1b–2 study was done at 16 centres in the USA. Patients were aged 18 years or older with diagnosis of multiple myeloma and Eastern Cooperative Oncology Group performance status of 1 or less with three or more previous lines of therapy, or were double refractory to a proteasome inhibitor and immunomodulatory drug, and had received a proteasome inhibitor, immunomodulatory drug, and anti-CD38 antibody. A single cilta-cel infusion (target dose 0·75 × 10 6 CAR + T cells per kg) was administered 5–7 days after lymphodepletion. Patient-reported outcomes were assessed using the European Organisation for Research and Treatment of Cancer (EORTC) quality of life questionnaire core 30-item, pre-specified items from the EORTC myeloma module, and EuroQol five-dimensional descriptive system questionnaire. Clinically meaningful changes in patient-reported outcomes were defined by anchor-based minimally important differences. This trial is registered with ClinicalTrials.gov, NCT03548207 . This trial is completed but feeding into a long-term follow-up study. Findings: Between July 16, 2018, and Oct 7, 2019, 78 patients were enrolled and underwent apheresis in phase 2 of the study. 68 patients were treated (43 [63%] male, 49 [72%] White), and their patient-reported outcomes assessed (median follow-up 16·9 months, IQR 15·7–17·5). After infusion, a transient decline was observed, followed by improvements in global health status (mean change from baseline to day 464 +8·0 points, SD 20·9), physical (+4·6 points, 21·1), and emotional functional scales (+1·9 points, 23·7) over time, and declines for symptom-based scores (−14·1 pain, SD 31·5 and –15·4 fatigue; SD 29·5), indicating improved patient HRQOL following treatment with cilta-cel. Interpretation: These durable HRQOL improvements are consistent with clinical findings, in which a single cilta-cel infusion led to substantial and durable responses in heavily pre-treated patients with relapsed or refractory multiple myeloma. These results support the use of cilta-cel in patients with relapsed or refractory multiple myeloma. Funding: Janssen Research & Development and Legend Biotech USA.